Some Developments and New Insights for Microseismic/Acoustic Emission Source Localization - Longjun Dong; Wei Zou; Daoyuan Sun; Xiaojie Tong; Xibing Li; Weiwei Shu (Shock and Vibration)
The purpose of this review is to discuss the development of the methods in microseismic/acoustic emission (AE) source localization and detail the principles of the mainly developed methods. The important applications of the microseismic/AE in engineering practice and the history of the source localization (from the initial Geiger method of localization to the later double-difference method) are introduced briefly in the beginning of the review. The factors that influence the accuracy of source locating are discussed in Section 2 to provide references on how to improve the accuracy of the localization methods. Then, the main localization methods in the history of the source and AE research have been classified into four parts (i.e., the localization methods for single event, the joint inversion methods, the relative localization methods, and the localization methods in spatial domain); each part is extended and systematically reviewed, respectively, from Sections 3 to 6, where the merit and demerit of the methods are discussed. Finally, a brief summary and some aspects of prospective research are presented.